Martyrologists without boundaries: the collaboration of John Foxe and Heinrich Pantaleon - Gehring, David S.; Freeman, Thomas S. (Cambridge University Press, 2018)
Amid the great Protestant martyrologies of the mid-sixteenth century, Heinrich Pantaleon’s Martyrvm historia (1563) has been comparatively overlooked. This article argues that Pantaleon’s martyrology acted as a capstone to the narrative framework of Protestant suffering and resistance. Pantaleon’s command of vernacular languages gave him access to a wider range of material than other martyrologists, material which his Latin text made accessible to learned readers across Europe. This article also examines the collaboration between Pantaleon and John Foxe, which directly inspired Pantaleon’s martyrology and enabled Foxe to give a cohesive, trans-European account of Protestant martyrs in his Acts and monuments.